Integration and Exchange: How Executive MBA Students Envision Ethics Education. (August 2013) - Gruber, Verena; Schlegelmilch, Bodo B.
Ethics education provided by universities in general, and MBA programs aimed at future business leaders in particular, has come under intense public scrutiny because of corporate scandals and ethical dilemmas. To date, academic research has been mainly devoted to the characteristics of instruction formats and their effectiveness, characteristics of the institutions (private, public, and/or religious affiliation), and the composition of the student body. Furthermore, the way business ethics is taught in MBA programs around the world has been influenced by recommendations of accreditation agencies and professional bodies. Against this background, this article aims to contrast these findings and recommendations with perceptions and expectations of experienced managers studying in part-time MBA programs. By means of 30 in-depth interviews conducted with MBA students of various nationalities studying at a well-known European business school, this research sheds light on an important but neglected perspective in the discussion surrounding ethics education, namely students' opinions. Findings indicate that exchange with others and integration within the respective business discipline is particularly important in gaining acceptance and instilling relevance in ethics education for this target group.